Traumatic Brain Injury Is Associated With Both Hemorrhagic Stroke and Ischemic Stroke: A Systematic Review and Meta-Analysis - Qu, Donghao; Li, Wenchen; Zhang, Shuyan; Li, Ri; Wang, Haifeng; Chen, Bo (Frontiers in Neuroscience, 2022)
Background Traumatic brain injury (TBI) is considered a risk factor for the development of stroke (Hemorrhagic Stroke and Ischemic Stroke). We performed this systemic review and meta-analysis to determine the association of prior TBI with the subsequent diagnosis of stroke. Methods We systematically searched PubMed, EMBASE, and the Cochrane Library for cohort studies involving TBI patients who subsequently developed stroke. Study selection, data extraction, and quality assessment were performed by two separate researchers. Data were analyzed with random-effects models, and a secondary analysis stratified by the type of stroke was performed. Results Of the 741 identified studies, 6 studies were eligible for inclusion, with more than 2,200,000 participants. TBI predicted the occurrence of stroke in the random-effect model, with a relative risk of 2.14 (95% CI 1.97–2.32, P < 0.001). Furthermore, in the analysis of each type of stroke, TBI was associated with the incidence of ischemic stroke (RR 1.351 95% CI 1.212–1.506, P < 0.001), and TBI was associated with an even greater increase in the incidence of hemorrhagic stroke (RR 6.118 95% CI 5.265–7.108, P < 0.001). Conclusion Our meta-analysis showed that TBI was associated with a more than two-fold increase in the risk of stroke. However, owing to the high degree of heterogeneity, decisions should be made on a patient-by-patient basis. The occurrence of TBI is associated with the development of both hemorrhagic and ischemic stroke, and the risk of hemorrhagic stroke is much higher than that of ischemic stroke in TBI patients.